IDENTIFIKASI ADAPTASI ARSITEKTUR TROPIS PADA BANGUNAN KOLONIAL STUDI KASUS: MUSEUM PERKEBUNAN INDONESIA - Buâ€™ulolo, Ferdinand F.; Silitonga, Shanty; Yulianto, . (Unika Santo Thomas, 2020)
Climate is the most important factor in architectural design, climate greatly influences the shape and appearance of buildings. Colonial buildings are buildings that have experienced a mix of European architects with local adaptation processes including the climate in Indonesia, one of which is the Indonesian Plantation Museum building in the city of Medan. Indonesia is included in a region that has a humid tropical climate, where the tropical climate has certain characteristics caused by solar heat, high humidity, rainfall, and wind movement. The purpose of this study is to identify aspects of tropicality in colonial buildings that have adapted to tropical climates. The method used in the study is the Case Study Qualitative Method with observation and identification of external forms (building orientation, roof, terraces and outside space) and the shapes in buildings (Patterns of Space, Floors, Walls, and Openings). The results of this study is the Indonesian Plantation Museum tends to be able to adapt to the local climate even though the shape and style of the building comes from Europeans,known as transition architecture. The building elements that are more adapted to the tropical climate are roofs with slopes of more than 30Âº, openings and cross ventilation, marble and wood floors and very thick concrete walls.